2021
DOI: 10.1186/s41938-021-00423-4
|View full text |Cite
|
Sign up to set email alerts
|

First report of three species of Trichoderma isolated from the rhizosphere in Algeria and the high antagonistic effect of Trichoderma brevicompactum to control grey mould disease of tomato

Abstract: Background Grey mould caused by Botrytis cinerea Pers. (teleomorph Botryotinia fuckeliana (de Bary) Whetzel) is one of the most destructive fungal diseases of Mediterranean crops. In Algeria, few studies have been made on the economic impact of this disease. Nevertheless, it is practically present in all tomato and strawberry greenhouses, as well as in prospected vineyards in the north and south of the country. The complexity of chemical control of this disease has led to search for Trichoderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…The tef 1α gene results showed sequence similarity of 98% with T. harzianum, whereas rpb2 showed 99% with T. afroharzianum (cryptic species of T. harzianum), respectively. Likewise, our investigation of the importance of rpb2 and tef 1α in validating the ITS results has been realized by many investigators [28].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The tef 1α gene results showed sequence similarity of 98% with T. harzianum, whereas rpb2 showed 99% with T. afroharzianum (cryptic species of T. harzianum), respectively. Likewise, our investigation of the importance of rpb2 and tef 1α in validating the ITS results has been realized by many investigators [28].…”
Section: Discussionmentioning
confidence: 66%
“…Studies on the effect of culture filtrate on the growth of some prominent phytopathogens viz., D. necatrix, F. oxysporum, F. solani and P. aphanidermatum revealed that their growth was significantly inhibited by chitinase producing isolated Trichoderma strains, concentrations and isolates differed significantly from each other among all the tested pathogens. Growth inhibition of the pathogens by Trichoderma culture-free filtrate has been reported by several workers [20,28]. The effect of culture filtrate of Trichoderma on the pathogen might be due to the production of chitinase [3,48] found that culture filtrates of T. harzianum inhibit zoospore germination, germ tube elongation and mycelial growth of P. aphanidermatum, causing damping-off disease of tobacco.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Their results indicated that Trichoderma strains reduce the mycelial growth of Foa isolates tested, with inhibition rates of 63% and 65% respectively. Due to their rapid development and their production of bioactive substances, several Trichoderma species limited the growth of Fusarium species and considered as a powerful microbial antagonists and can be used as a bioprotector or as a plant biostimulant (Sghir et al, 2016;Benouzza et al, 2020;Haouhach et al, 2020;Bustamante et al, 2021;Pani et al, 2021;Hammad et al, 2021). In the same context, the efficacy in vitro of the inhibitory activity of T. harzianum against F. oxysporum were assessed by Hibar et al (2005) who recorded inhibition rates greater than 65%, after a direct confrontation on the PDA medium.…”
Section: Comparison Of Inhibition Meansmentioning
confidence: 99%
“…(Suganda., 2020) Through the dual culture test, three types of Trichoderma isolated from the tomato rhozosphere were able to suppress soilborne pathogens by 65%. (Hammad et al, 2021). reported that Trichoderma asperellum which is a rhizosphere fungus on Malus sieversisi can suppress the pathogen Fusarium oxsysporum (FOX68) by 66.7%.…”
Section: Introductionmentioning
confidence: 99%